Monetary and Fiscal Policy in a Large Asymmetric Monetary Union - A Dynamic Three-Country Analysis - Volker Clausen; Hans-Werner Wohltmann (Kiel University, Department of Economics, 2005)
This paper analyzes the dynamic effects of anticipated monetary and fiscal policies in a large monetary union, which is characterized by asymmetric interest rate transmission. We explicitly solve the asymmetric three-country model using the decomposition methods of Aoki (1981) and Fukuda (1993). Anticipated monetary and fiscal expansions lead to negative international spillovers and to intertemporal reversals in the relative effectiveness of policy on member country outputs. Intertemporal international coordination of monetary policies between Euroland and the US is able to stabilize the output adjustment processes induced by an anticipated unilateral fiscal expansion.
Keywords: F41; E58; 330; Monetary Union; Fiscal Policy; Monetary Policy; Policy Coordination; Geldpolitik; Finanzpolitik; Währungsunion; Mehr-Länder-Modell; Konjunkturzusammenhang; Internationale wirtschaftspolitische Koordination; Europäische Wirtschafts- und Währungsunion; Theorie; USA; EU-Staaten